The Impact of Gold Price and Us Dollar Index: The Volatile Case of Shanghai Stock Exchange and Bombay Stock Exchange During the Crisis of Covid-19 - Kumar, Joseph John Allwyn; Robiyanto, Robiyanto (University of Merdeka Malang, 2021)
This literature aims to analyze the impact of the Dollar Index and Gold Price returns and volatility on stock market volatility of India and China, viz., Shanghai Stock Exchange and Bombay Stock Exchange Sensex, during the period of Covid-19. This study employs daily time-series data from January up to August for 2019, 2020, and a merged data of 2019-2020, i.e., Pre-Pandemic, Mid-Pandemic and Pre through Mid-Pandemic periods, respectively; to avoid possible abnormalities and heteroscedasticity, the GARCH (1,1) model is utilized to scrutinize the data depending on which distribution is more acceptable, GED or Gaussian, which is decided based on the Unit-Root and normality test results. The findings of this study prove that Gold Price mostly does have a significant effect on both markets, especially during times of financial crisis like the Covid-19 epidemic. Whereas Dollar Index has a significant impact on emerging markets such as India and China though significant effects persist in some cases, it is not valid in most cases.DOI: 10.26905/jkdp.v25i3.5142